Entrepreneurs' Perception of Their Skills and the Influence of Education on the Romanian Entrepreneurial System - Mirela Octavia Sîrbu; Constantin Bob; Andreea Simona Săseanu (Amfiteatru Economic Journal, 2015)
The business environment can provide entrepreneurs with an adequate or restrictive framework by the existence or, on the contrary, the absence of legal, economic, social and politic facilities. In this sense, its analysis becomes a continuous necessity and, at the same time, a premise for the viability of the company. Starting from these grounds, this paper is aimed at investigating the relation between the entrepreneurial system and the business environment through selective research regarding the motivational aspects and the economic premises for the initiation and operation of companies in the Romanian business environment. Performed on a sample of 276 entrepreneurs, via a questionnaire, the main objectives of the research were to estimate the influence exerted by the main characteristics of business environment on the foundation of a company and to identify the characteristics of entrepreneurs in order to develop an entrepreneur profile. Due to the defining importance of entrepreneurial education, the research was focused on the identification and assessment of the skills that the investigated entrepreneurs possessed. The originality of the paper is given by the identification of the entrepreneurs' characteristics and skills tightly correlated with the idiosyncrasies of Romanian business environment.
Keywords: L26; M13; P46; 330; business foundation; business environment; entrepreneurial skills; motivational variables